2006
DOI: 10.1097/01.cad.0000215063.23932.02
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of quercetin in the human U138MG glioma cell line

Abstract: Recent epidemiological and dietary intervention studies in animals and humans have suggested that diet-derived flavonoids, in particular quercetin, may play a beneficial role by preventing or inhibiting tumorigenesis. The aim of this study was to evaluate whether quercetin may act differently on cancer and normal neuronal tissue. In order to investigate this, the U138MG human glioma cell line and hippocampal organotypic cultures were used. The study showed that quercetin induced in glioma cell cultures results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 32 publications
4
60
0
2
Order By: Relevance
“…Quercetin led to a G2 cell-cyle arrest accompanied by a reduction of mitotic rate (Braganhol, Zamin et al, 2006). In addition, this group was able to show that ischemic damage to hippocampal slice cultures was attenuated by quercetin (Braganhol, Zamin et al, 2006). These results are in so far exciting as quercetin obviously exerts anti-cancer effects on one of the most highly therapeutic resistant tumor, glioblastoma, while at the same concentrations it exhibits neuro-protection to oxygen-sensitive hippocampal neuronal cells.…”
Section: Polyphenols As a Novel Treatment Options For Gliomassupporting
confidence: 61%
See 2 more Smart Citations
“…Quercetin led to a G2 cell-cyle arrest accompanied by a reduction of mitotic rate (Braganhol, Zamin et al, 2006). In addition, this group was able to show that ischemic damage to hippocampal slice cultures was attenuated by quercetin (Braganhol, Zamin et al, 2006). These results are in so far exciting as quercetin obviously exerts anti-cancer effects on one of the most highly therapeutic resistant tumor, glioblastoma, while at the same concentrations it exhibits neuro-protection to oxygen-sensitive hippocampal neuronal cells.…”
Section: Polyphenols As a Novel Treatment Options For Gliomassupporting
confidence: 61%
“…Quercetin led to a G2 cell-cyle arrest accompanied by a reduction of mitotic rate (Braganhol, Zamin et al, 2006). In addition, this group was able to show that ischemic damage to hippocampal slice cultures was attenuated by quercetin (Braganhol, Zamin et al, 2006).…”
Section: Polyphenols As a Novel Treatment Options For Gliomasmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been reported that quercetin in low concentration promoted cell proliferation of A-549 cells, whereas in higher concentration it inhibited cell proliferation and survival [43]. Further quercetin exerted antiproliferative effect against glioma and breast cancer cells [44][45][46]. Acacetin, another important flavanoid inhibited the proliferation of A549 cells, induced apoptosis and blocked the cell cycle progression at G1 phase.…”
Section: Role Of Antioxidant In Preventing Cancermentioning
confidence: 99%
“…Recent studies have investigated the anti-oncogenic properties of natural products and several of these studies have shown that natural product extracts exhibit anti-oncogenic properties against various types of cancer [3][4][5][6][7]. Specifically, there has been a renewed effort to examine the anti-oncogenic properties of natural products for the treatment of GBM cells [8][9][10][11][12][13]. However, the anti-oncogenic properties of rosehip extracts on GBM cells have not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%